1994
DOI: 10.1080/03079459408419016
|View full text |Cite
|
Sign up to set email alerts
|

A syndrome associated with growth depression and amyloid arthropathy in layers: A preliminary report

Abstract: SUMMARYIn heavy breed layers a new syndrome was encountered, associated with impaired growth. The disease developed from 5 to 6 weeks onwards. Morbidity in most flocks was 1 to 4%, but in some cases up to 20%. The affected birds were smaller in size, made a peeping sound like that of younger chickens, and showed a characteristic stiff gait. The stifle and hock joints were swollen. At necropsy 12 out of 66 affected birds (18%) had bronze-coloured livers and 23 out of 66 (35%) had orange-coloured joint deposits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 23 publications
4
70
1
Order By: Relevance
“…55 Chicken AA amyloidosis is referred to as amyloid arthropathy and is associated with Enterococcus faecalis infection, while spontaneous chicken systemic AA amyloidosis is less common. 33,65,80 Induced Avian Amyloidosis. Birds raised for human consumption may be subject to stressful environmental conditions and occasionally develop AA amyloidosis.…”
Section: Transmission Of Avian Aa Amyloidosismentioning
confidence: 99%
“…55 Chicken AA amyloidosis is referred to as amyloid arthropathy and is associated with Enterococcus faecalis infection, while spontaneous chicken systemic AA amyloidosis is less common. 33,65,80 Induced Avian Amyloidosis. Birds raised for human consumption may be subject to stressful environmental conditions and occasionally develop AA amyloidosis.…”
Section: Transmission Of Avian Aa Amyloidosismentioning
confidence: 99%
“…Pathogenesis of amyloidosis in hens can not be fully explained yet (Landman et al 1998b). SAA is a major acute phase reactant in the blood and its level increases after various insults to the body (Landman et al 1994, Urieli-Shoval et al 2000. Some studies in recent years revealed the importance of SAA in monitoring poultry health (Chamanza et al 1999, Upragarin et al 2005b.…”
Section: Discussionmentioning
confidence: 99%
“…Birds were then killed, using an electric current (10 s at 340 V) and bled. Bacteriological examination of the ovary, oviduct, and knee joints was performed as described (5). For bacteriological examination of blood, ChromocuV Enterococci Broth (Merck KG&A, Darmstadt, Germany) and BBL® Vacutainer® Brand culture bottles for blood cultures (Becton Dickinson Microbiology Systems, Maryland, USA) were used.…”
Section: Materials and Methods Parent Flock And Experimental Designmentioning
confidence: 99%